FAKTOR-FAKTOR YANG MEMPENGARUHI TINDAKAN MASYARAKAT DALAM PENCEGAHAN COVID-19 DI KABUPATEN BANYUMAS - Aviva Anggraeni; Aisyah Apriciciliana Aryani; Dian Anandari (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Background : Covid-19 is an infectious disease and has been declared a global pandemic. The spread of Covid-19 in Banyumas Regency is increasingly widespread. Precautions were taken to reduce Covid-19 cases. This study aims to know the factors that influence community actions in preventing Covid-19 using logistic regression analysis. Method : Cross-sectional design with a sample of 188 people obtained by incidental sampling method. The questionnaire instrument used a google form questionnaire. The analysis was carried out until the logistic regression test stage. Result : From 188 people who were the respondent of research were people with the adult age category of 95.2%, female sex 81.4%, high school education 69.7%, employment as a student status 65.4%, sources of information obtained from mass media 53.2%. Good knowledge 62.8%, positive attitude 51.1%, supportive family support 51.6%, good preventive action 63.3%. The results of the logistic regression analysis show that the factors that influence the Covid-19 prevention measures are family support (p-value = 0.000, OR = 10,776, 95% Cl = 4,782-24,282). Conclusion : Age, occupation, and sources of information have no relationship with Covid-19 prevention measures. However, gender, education, knowledge, attitudes, and family support have a relationship with Covid-19 prevention measures. Family support is the factor that most influences Covid-19 prevention measures.